Recent Hydrological Droughts in Brazil and Their Impact on Hydropower Generation - Cuartas, Luz Adriana [UNESP]; Cunha, Ana Paula Martins Do Amaral [UNESP]; Alves, Jessica Anastácia [UNESP]; Parra, Larissa Milena Pinto [UNESP]; Deusdará-Leal, Karinne; Costa, Lidiane Cristina Oliveira; Molina, Ruben Dario; Amore, Diogo; Broedel, Elisangela; Seluchi, Marcelo Enrique; Cunningham, Christopher; Alvalá, Regina Célia Dos Santos [UNESP]; et al. (MDPI, 2022)
Brazil has endured the worst droughts in recorded history over the last decade, resulting in severe socioeconomic and environmental impacts. The country is heavily reliant on water resources, with 77.7% of water consumed for agriculture (irrigation and livestock), 9.7% for the industry, and 11.4% for human supply. Hydropower plants generate about 64% of all electricity consumed. The aim of this study was to improve the current state of knowledge regarding hydrological drought patterns in Brazil, hydrometeorological factors, and their effects on the country’s hydroelectric power plants. The results show that since the drought occurred in 2014/2015 over the Southeast region of Brazil, several basins were sharply impacted and remain in a critical condition until now. Following that event, other regions have experienced droughts, with critical rainfall deficit and high temperatures, causing a pronounced impact on water availability in many of the studied basins. Most of the hydropower plants end the 2020–2021 rainy season by operating at a fraction of their total capacity, and thus the country’s hydropower generation was under critical regime.
Keywords: Drought monitoring; Hydrological drought; Hydrometeorological extreme; Hydropower generation